Geopolymer-hydrotalcite composites for CO2 capture. (10th November 2019) - Papa, E.; Medri, V.; Paillard, C.; Contri, B.; Natali Murri, A.; Vaccari, A.; Landi, E.
Abstract: Supporting or shaping a porous powder is important for industrial applications as optimized structure with high mass transfer, low pressure drop and high mechanical and chemical stability can be obtained. A new class of geopolymer-hydrotalcite composites with suitable mechanical and thermal properties were conceived as shaped materials for CO2 adsorption applications at intermediate temperature (200–400 °C). Composite monoliths were produced mixing different commercial hydrotalcite-type (HyT) powders with a metakaolin-based geopolymer matrix with a molar ratio SiO2 :Al2 O3  = 4.0. The compressive strength at room temperature and 500 °C ranged between 10 and 35 MPa, mainly depending on HyT powder morphology and composite total porosity. The composites were characterized and tested in term of CO2 uptake. After calcination to convert HyT into an amorphous Mg:Al mixed solid oxide able to absorb CO2, the composites were tested in the CO2 adsorption at 200 °C, with cycles of adsorption/desorption performed with intermediate regeneration at 500 °C. CO2 adsorption capacity was in the range 0.375–0.461 mmol g −1 for HyT and between 0.109 and 0.145 mmol g −1 for composites, being 0.052 mmol g −1 the value for the geopolymer matrix. A partial deactivation of the HyT phases was also detected. Highlights: Geopolymer-hydrotalcite composites were developed for CO2 uptake at 200 °C. A partial deactivation of the hydrotalcite-type phases occurred in composites. The contribution of physical reversible adsorption was ∼50% in composites. The composites showed compressive strength at r.t. and 500 °C in the rage of 10–35 MPa.